2020
DOI: 10.21873/invivo.11814
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Goose-beak Bone Particles for Dentoalveolar Reconstruction in Dogs

Abstract: Background/Aim. Tooth extraction is a common procedure in dental clinics. Tooth extraction can destroy gingiva, alveolar bone, periodontal ligaments and cement. If dental sockets are left as extracted, it will result in loss of teeth, as well as voice and aesthetic problems. A natural hydroxyapatite (HA) bioceramic bone graft substitute developed from goose-beak bone particles (GBPs) was used for dentoalveolar reconstruction in a canine model. Materials and Methods: Four adult (18-22 months old) male beagle do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In a study by Jang and Choi, 131 eight alveolar extraction sockets from four dogs were arbitrarily assigned into two groups to ascertain a split‐mouth architecture with the following treatment: control group, sockets filled with commercially purchased synthetic HA; Test group, sockets filled with grainy pounds. The results showed that the natural ceramic powder derived from GBP is suitable for canine alveolar bone reconstruction 131 . Inomata et al 132 extracted all premolars in beagle dog mandibles bilaterally.…”
Section: Implantation Defect Models (Include Alveolar Ridge Expansion...mentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Jang and Choi, 131 eight alveolar extraction sockets from four dogs were arbitrarily assigned into two groups to ascertain a split‐mouth architecture with the following treatment: control group, sockets filled with commercially purchased synthetic HA; Test group, sockets filled with grainy pounds. The results showed that the natural ceramic powder derived from GBP is suitable for canine alveolar bone reconstruction 131 . Inomata et al 132 extracted all premolars in beagle dog mandibles bilaterally.…”
Section: Implantation Defect Models (Include Alveolar Ridge Expansion...mentioning
confidence: 99%
“…The results showed that BM led to more successful bone regeneration during GBR, in particular, CM was used in combination as a barrier to promote the regeneration of canine alveolar ridge defects 130 . In a study by Jang and Choi, 131 eight alveolar extraction sockets from four dogs were arbitrarily assigned into two groups to ascertain a split‐mouth architecture with the following treatment: control group, sockets filled with commercially purchased synthetic HA; Test group, sockets filled with grainy pounds. The results showed that the natural ceramic powder derived from GBP is suitable for canine alveolar bone reconstruction 131 .…”
Section: Implantation Defect Models (Include Alveolar Ridge Expansion...mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, critical bone defects are more serious. For the reconstruction of such defects, autografts, allografts, or xenografts have been used (1). Although autografts are good for inducing osteoinduction and osteoconduction, such grafts are limited to filling small defects because they are limited by the amount of tissue that can be obtained.…”
mentioning
confidence: 99%